A decision-making model for selecting product suppliers in crop protection retail sector - Byungok Ahn; Bo-Young Kim (Administrative Sciences, 2023)
This study aims to determine the importance of factors affecting supplier selection in the pesticide distribution sector as a global emerging market and present a decision-making model for the corporate marketing strategy. Specifically, a comparative study between suppliers and retail distribution experts was conducted to compare differences in the perception of supplier selection factors according to organizational characteristics. Based on previous studies, a decision-making model based on the AHP methodology was constructed with a total of 20 factors in five areas: product quality, price, flexibility, promotion support, and brand. Then, 42 Korean experts were surveyed to measure the importance of these factors. The results showed that product quality is the most critical factor in supplier selection, followed by price, brand, promotional support, and flexibility, in that order. Manufacturers consider product quality as the most important factor, while retailers consider price as the most important factor. Among the 20 factors, "quality excellence", "expected return", and "technological competitiveness" were found to be the most important factors. In addition, while manufacturers considered factors such as "corporate reputation" and "corporate trust" as more important, retailers considered factors related to product characteristics, such as 'product awareness' and "brand reputation" as more important.
Keywords: 350; crop protection; emerging market; marketing strategy; product supplier; retailer